Hierarchical Polyelemental Nanoparticles as Bifunctional Catalysts for Oxygen Evolution and Reduction Reactions. Issue 25 (12th May 2020) - Wu, Meiling; Cui, Mingjin; Wu, Lianping; Hwang, Sooyeon; Yang, Chunpeng; Xia, Qinqin; Zhong, Geng; Qiao, Haiyu; Gan, Wentao; Wang, Xizheng; Kline, Dylan; Zachariah, Michael R.; et al.
Abstract: Efficient electrocatalysts are critical in various clean energy conversion and storage systems. Polyelemental nanomaterials are attractive as multifunctional catalysts due to their wide compositions and synergistic properties. However, controlled synthesis of polyelemental nanomaterials is difficult due to their complex composition. Herein, a one‐step synthetic strategy is presented to fabricate a hierarchical polyelemental nanomaterial, which contains ultrasmall precious metal nanoparticles (IrPt, ≈5 nm) anchored on spinel‐structure transition metal oxide nanoparticles. The polyelemental nanoparticles serve as excellent bifunctional catalysts for the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). The mass catalytic activity of the polyelemental nanoparticles is 7‐times higher than that of Pt in ORR and 28‐times that of Ir in OER at the same overpotentials, demonstrating the high activity of the bifunctional electrocatalyst. This outstanding performance is attributed to the controlled multiple elemental composition, mixed chemical states, and large electroactive surface area. The hierarchical nanostructure and polyelemental design of these nanoparticles offer a general and powerful alternative material for catalysis, solar cells, and more. Abstract : A hierarchical polyelemental nanomaterial of ultrasmall precious metal nanoparticles (IrPt) anchored on spinel‐structure transition metal oxide nanoparticles is synthesized via a one‐step method. Benefitting from the nanostructure of hierarchy and polyelements, it is demonstrated as a highly efficient and stable bifunctional electrocatalyst for the oxygen reduction reaction and the oxygen evolution reaction.